Facile synthesis of carbon layer-entangled Fe2O3 clusters as anode materials for improved Li-ion batteries - Oh, Hang-Deok; Lee, Sang-Wha; Kim, Sang-Ok; Lee, Joong Kee (Elsevier BV, 2013)
Carbon layer-entangled iron oxides (Fe2O3@carbon) are facilely prepared through the cross-linking assembly of iron oxides induced by the addition of 1,12-diaminododecane (C-12 diamines). The calcined Fe2O3@carbon composites exhibit the XRD patterns attributed to hexagonal phase of hematite (alpha-Fe2O3) with negligible magnetism. As anode electrode materials for Li-ion batteries, the Fe2O3@carbon exhibits the retained capacity of 614 mAh g(-1) at 0.1 C after 35 cycles, while the carbon free Fe2O3 exhibits the retained capacity of 283 mAh g(-1) at 0.1 C after 35 cycles. The unique formation of carbon layer entanglement within iron oxide clusters contributes the improved capacity retention capability of the composite electrode (Fe2O3@carbon) by providing buffering space for large volume expansion and enhanced electrical conductivity between the active iron oxides. (C) 2013 Elsevier B.V. All rights reserved.